Variation in the Outcome of Norepinephrine-Dependent Septic Patients After the Institution of a Patient-Tailored Therapy Protocol in an Italian Intensive Care Unit: Retrospective Observational Study - Casarotta, Erika; Damiani, Elisa; Domizi, Roberta; Carsetti, Andrea; Scorcella, Claudia; Adrario, Erica; Bolognini, Sandra; Di Falco, Domenico; Pantanetti, Simona; Vannicola, Sara; Damia Paciarini, Agnese; Donati, Abele (Frontiers in Medicine, 2020)
Objective: To evaluate the outcome of patients with septic shock after the institution of a patient tailored therapy protocol in our Intensive Care Unit (ICU). Methods: Single-centre retrospective observational study including 100 consecutive patients (≥ 16 years) diagnosed with septic shock, according to the 2001 International Sepsis Definition Conference criteria, admitted to our ICU between 2018-2019 after the institution of a patient-tailored therapy protocol, compared with a historical control group of 100 patients admitted between 2010-2013 (standard therapy). The patient-tailored therapy protocol included the use of IgM-enriched immunoglobulins for patients with low plasma IgM levels, blood purification strategies for patients with high plasma levels of cytokines or endotoxin, albumin correction and modulation of vasoactive agents. Clinical and therapeutic parameters were noted at the time of septic shock diagnosis and for the first 24 hours. The primary outcome was ICU mortality. Results: ICU-mortality was lower in the patient-tailored therapy cohort as compared to the standard therapy cohort (32% versus 57%, p<0.001). Patient-tailored therapy was associated with a lower risk of ICU-mortality even after adjusting for the main clinical severity indices (adjusted odds ratio 0.273 [95% confidence interval 0.132-0.566], p<0.001). After propensity score matching, 54 patients in the standard cohort and 54 patients in the patient-tailored therapy cohort with similar general characteristics were selected. ICU-mortality was lower in the patient-tailored therapy matched subgroup as compared to the standard therapy subgroup (31.5% versus 55.6%, p=0.019). Conclusions: An individualised therapeutic approach in septic patients may be associated with a survival benefit. However, the use of an historical control group of patients admitted between 2010 and 2013 may introduce substantial bias. Further adequately designed studies are needed to demonstrate the impact of patient-tailored therapy on outcome.